Media Relations Activities At Polytechnic Lp3I Bandung - Pandre, Asdo; Jamilus, Jamilus (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
media relationsas part of external public relations activities is a step to foster good relations between companies or institutions and their publics. This activity was carried out with the aim of forming a positive public opinion for the institution. In addition, this activity is intended as a promotional vehicle that is profitable for the institution. This was also carried out by the Bandung LP3I Polytechnic institution working together to build good and mutually beneficial relationships with members of the press, both print and electronic media. This study uses a qualitative approach with descriptive analysis method. Data collection techniques used are interviews and documentation studies. In this study, it reveals about media relations activities and strategies in dealing with journalists with the aim of maintaining good relations. In the concept of Media Relations, superiors and subordinates are not recognized, but the relationship that exists between the two is called a partnership. There is also a relationship with members of the press at the Bandung LP3I Polytechnic, namely the marketing division. The results of the research show that the media relations activities that have been carried out so far have been running quite well. Of the seven media relations activities carried out, five of them were carried out well, while the rest had not been carried out due to the campus's internal activities. Even though the two Media relations activities have not been carried out, it does not mean that the relationship that has existed so far has become bad. This is not a significant problem, but the parties do not underestimate the problem, and wish to apply this activity in the future. Meanwhile, the strategy for dealing with journalists carried out by the marketing division was carried out very well. It can be seen that there is no conflict between marketing and journalists.